Pengaruh Kualitas Produk dan Promosi Diskon Terhadap Keputusan Pembelian Konsumen Produk Gamis Alariseproject pada Marketplace Shopee - Zafira Nurtadza Putri; Halimah Zahrah; Indra Sasangka (Indo Publishing, 2026)
The growth of e-commerce in Indonesia, particularly the Muslim fashion sector, has experienced rapid growth in line with increasing internet penetration and consumer demand. Product quality and discount promotions are seen as important factors influencing consumer purchasing decisions on e-commerce platforms like Shopee. This study aims to analyze how product quality and discount promotions influence consumer purchasing decisions for gamis products on Shopee. The study used a quantitative approach through a survey of consumers who had previously made purchases. The results show that good product quality can increase consumer confidence and satisfaction, while discount promotions encourage purchase interest and accelerate purchase decisions. Together, these two factors contribute significantly to shaping consumer purchasing decisions on Shopee.